Metastatic Ovarian Tumors Originating From a Small Bowel Adenocarcinoma – A Case Report and Brief Literature Review. (May 2017) - Mitsushita, Junji; Netsu, Sachiho; Suzuki, Koichi; Nokubi, Mitsuhiro; Tanaka, Akira
Abstract : Approximately 1.6% of tumors metastatic to the ovary of nongynecologic origin are from a small bowel adenocarcinoma (SBA). However, the incidence of SBA is extremely rare (0.23 cases/100, 000 people), which suggests a high frequency of ovarian metastasis, although the reason is unknown. To identify the characteristics of ovarian tumor metastasis from SBA, we reviewed 72 cases reported in the English literature, including the case presented in this report. The mean age of the patients was 46.7 yr. Solitary ovarian metastasis was observed in 67% of the cases, and ovarian metastasis was accompanied by peritoneal dissemination in 33% of the cases. Although duodenal adenocarcinoma has the highest incidence among the SBAs, jejunal adenocarcinoma, particularly that at the proximal end, is the type of SBA that most frequently metastasizes to the ovary. Among the cases of ovarian metastasis from SBA, 51% were bilateral, 33% were unilateral to the right ovary, and 16% were unilateral to the left ovary.